Measurements of Groomed-Jet Substructure of Charm Jets Tagged by D0 Mesons in Proton-Proton Collisions at s =13 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (American Physical Society, 2023)
Understanding the role of parton mass and Casimir color factors in the quantum chromodynamics parton shower represents an important step in characterizing the emission properties of heavy quarks. Recent experimental advances in jet substructure techniques have provided the opportunity to isolate and characterize gluon emissions from heavy quarks. In this Letter, the first direct experimental constraint on the charm-quark splitting function is presented, obtained via the measurement of the groomed shared momentum fraction of the first splitting in charm jets, tagged by a reconstructed D^{0} meson. The measurement is made in proton-proton collisions at sqrt[s]=13 TeV, in the low jet transverse-momentum interval of 15≤p_{T}^{jet ch}
Keywords: Physics; Particle physics; Charm quark; Nuclear physics; Quark; Gluon; Parton; Jet (fluid); Parton shower; Perturbative QCD; Charm (quantum number); Proton; Quark–gluon plasma; Meson; Quantum chromodynamics; https://purl.org/pe-repo/ocde/ford#1.03.03